Postural balance during quiet stance and standing shooting position in biathletes - Sadowska, D.; Sacewicz, T.; Lichota, M.; Krzepota, J. (Acta Kinesiologica, 2020)
Postural balance is crucial for shooting accuracy and often determines the biathlete`s final result during the competition. The aim of the study was to (1) examine the postural balance of 11 biathletes and 12 physically active, untrained subjects during quiet stance in four conditions (standing in footwear with eyes open, standing in footwear with eyes closed, standing barefoot with eyes open, and standing barefoot with eyes closed) and (2) assess postural balance in biathletes in the standing shooting position. Postural balance was examined using the Zebris FDM-2 Force Distribution Measuring System. Biathletes had a significantly better stance stability, as evidenced by less body sways during the quiet stance than non-athletes. In both groups, the footwear did not significantly affect the postural balance parameters. Eye closure caused similar increase in postural balance parameters in biathletes and non-athletes, which confirms a significant contribution of visual information to postural balance control comparable in both groups. The standing shooting position of biathletes is characterized by greater body sways in the cross-shooting direction than in the shooting direction.